Development of one cycle current controller using raspberry Pi for 3 phase active power filter for nonlinear load improvement - Mohamad Shari, Mohd Hafiz (2015)
Nowadays, Power distribution systems are faces more challenging problems of nonlinear load form commercial building and domestic use. The problem occurs when every single electronic appliances or electronic power supply used rectifier as a new conversion technologies such as Switch Mode Power Supply (SMPS) and it can be found virtually in every power electronic devices. The effect of nonlinear loads are create harmonic current in additional to the fundamental AC current waveform and transform the shape of the current from sine wave to some other form such as “double-hump”, and it can affect both the distribution system equipment and the loads connected to it. Therefore this study is proposing a solution by development of one cycle current control (OCC) using Raspberry Pi for 3 phases Active Power Filter where the main objective are to harmonic elimination and power quality improvement. The model was perform in MATLAB/Simulink and also implements the hardware by using Raspberry Pi as a digital signal processing system. The result and analysis of the performance were explained in this report in terms of the output current waveform and the effect of nonlinear load through the 3 phase power supply. Finally, the harmonic compensating efficiency to the typical non-linear loads of the approach presented is further verified by implementation of the One Cycle Current Controller (OCC) is designed by simulation and hardware experimental results are presented.